2022
DOI: 10.3390/jcm11247425
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Needle Aspiration vs. Surgical Incision of Parotid Abscesses

Abstract: Objective: Standard treatment of parotideal abscesses consists of surgical drainage. This often has to be carried out in general anesthesia and carries the risk of iatrogenic injury of the facial nerve. Ultrasound-guided needle aspiration is an alternative therapy. Up until now a lack of systematic data concerning this subject exists. The study at hand aims to answer the question whether needle aspiration is a viable alternative for surgical drainage. Methods: All patients who had been treated surgically (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Minimally invasive techniques, such as ultrasoundguided puncture drainage, have been used to treat abscesses of the head and neck, even some DNAs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Ultrasound-guided puncture drainage can avoid the above drawbacks of surgical incision drainage and provide several advantages. First, ultrasound-guided puncture drainage can accurately locate the DNAs, eliminating trauma to the neighbouring vital structures and avoiding tumour dissemination during surgical incision.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Minimally invasive techniques, such as ultrasoundguided puncture drainage, have been used to treat abscesses of the head and neck, even some DNAs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Ultrasound-guided puncture drainage can avoid the above drawbacks of surgical incision drainage and provide several advantages. First, ultrasound-guided puncture drainage can accurately locate the DNAs, eliminating trauma to the neighbouring vital structures and avoiding tumour dissemination during surgical incision.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several studies have shown that ultrasound-guided puncture drainage is a more effective option than surgical incision drainage for some DNAs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In addition, ultrasound-guided puncture drainage can reduce the length of hospital stay. [25][26][27][28][29] However, most of these studies were case series, reviews and retrospective studies, and prospective and randomised controlled trials are rare.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations